STRATEGI PENANGGULANGAN LAMA GENANGAN AIR BERDASARKAN SISTEM EVALUASI - Enteding, Trianto; Andini, Nurul; Katili, Hidayat Arismunandar; Ada, Camelia Citra (Fakultas Pertanian Universitas Tompotika Luwuk, 2025)
Rice fields are a highly strategic form of land use because they are the main resource for producing rice. Rice is a crop that grows well in flooded conditions. However, above-normal flooding will also affect the condition of the rice plants themselves. Climate change, erratic rainfall and inadequate drainage infrastructure often cause prolonged flooding. Minakarya Village is one of the centres of rice (Oryza sativa L.) production in Moilong Subdistrict, Banggai Regency. Currently, the problem faced in rice paddy production is a decline in productivity due to excessive waterlogging, which causes damage to the land. Therefore, this study aims to formulate strategies for managing rice fields in Minakarya Village, Moilong. managing rice fields in Minakarya Village, Moilong Subdistrict, Banggai Regency. This study also uses the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis method to evaluate internal and external factors that influence waterlogging problems and formulate relevant strategies. The results of this study show that the recommended strategies for overcoming waterlogging in rice fields in Minakarya Village include improving drainage, applying modern technology, and selecting rice varieties that are resistant to waterlogging.